The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/catal9090717
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study Based on the Carbide Mechanism of a Co-Pt/γ-Al2O3 Fischer–Tropsch Catalyst Tested in a Laboratory-Scale Tubular Reactor

Abstract: A Co-Pt/γ-Al2O3 catalyst was manufactured and tested for Fischer–Tropsch applications. Catalyst kinetic experiments were performed using a tubular fixed-bed reactor system. The operative conditions were varied between 478 and 503 K, 15 and 30 bar, H2/CO molar ratio 1.06 and 2.11 at a carbon monoxide conversion level of about 10%. Several kinetic models were derived, and a carbide mechanism model was chosen, taking into account an increasing value of termination energy for α-olefins with increasing carbon numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…They also proposed a pseudo-homogenous one-dimensional model to evaluate the kinetic performance of the catalyst and achieved less than 8% error with the predicted data for kinetic experiments [95]. More recently, Marchese et al, performed kinetic studies with Co-Pt/γ-Al 2 O 3 catalyst in a lab-scale tubular reactor and reported an error band around ± 25% with a confidence level of 0.95 stating it lies in the suitable acceptable limits with many mechanistic models proposed in the literature [89,[96][97][98].…”
Section: Ft Kinetic Modelmentioning
confidence: 85%
“…They also proposed a pseudo-homogenous one-dimensional model to evaluate the kinetic performance of the catalyst and achieved less than 8% error with the predicted data for kinetic experiments [95]. More recently, Marchese et al, performed kinetic studies with Co-Pt/γ-Al 2 O 3 catalyst in a lab-scale tubular reactor and reported an error band around ± 25% with a confidence level of 0.95 stating it lies in the suitable acceptable limits with many mechanistic models proposed in the literature [89,[96][97][98].…”
Section: Ft Kinetic Modelmentioning
confidence: 85%
“…For both biogas-derived CO 2 and digestate, economic considerations were accounted for the production of FT waxes (Marchese, 2021). For all the analyzed processes, the production of FT compounds is described by a mechanistic kinetic model validated with experimental results (Marchese et al, 2019). Figure 4 provides the schematics of the process models taken into consideration for the evaluation of the FT production potential throughout Europe.…”
Section: Reference Ccu Plant Configurationsmentioning
confidence: 99%
“…A detailed description of the CCUto-FT plant together with an energy analysis can be found at [9,14]. The FT synthesis accounted for a carbide mechanistic kinetic model for the description of the FT products generation [15].…”
Section: System Optimizationmentioning
confidence: 99%